2021
DOI: 10.1016/j.jretconser.2020.102341
|View full text |Cite
|
Sign up to set email alerts
|

Has financial attitude impacted the trading activity of retail investors during the COVID-19 pandemic?

Abstract: Financial attitude influences the financial behavior of retail investors. Although the extant research has acknowledged and examined this relationship, the measures of financial attitude and behavior still vary widely and are generally posed as a series of questions rather than statements. In addition to this, there is insufficient knowledge regarding retail investors' behavior in the face of a health crisis, such as the current COVID-19 pandemic. This study addresses these gaps in the prior literature by exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 191 publications
(182 citation statements)
references
References 82 publications
5
140
0
6
Order By: Relevance
“…Thesefindings support and strengthens previous studies related to the influence of investment motivation and financial literacy in determining interest in investingin the capital market. These findings corroborate Planned Behavior Theory as reviewed in several previous research [4], [17].…”
Section: Multiple Linear Regressionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thesefindings support and strengthens previous studies related to the influence of investment motivation and financial literacy in determining interest in investingin the capital market. These findings corroborate Planned Behavior Theory as reviewed in several previous research [4], [17].…”
Section: Multiple Linear Regressionsupporting
confidence: 92%
“…Indonesian Stock Exchange investors who have a high level of financial literacy tend to increase their investment interest. The period of the COVID-19 pandemic has not reduced their interest in investing, this is relevant to research results in a number of other countries [4], [10].…”
Section: Multiple Linear Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…47,48 During the COVID-19 pandemic, there was enormous and abundant of information on social media which lead to potential information overload and triggered a lot of negative behaviour. 8,49 It has been shown that when humans are overloaded by information, it leads to fatigue, 50 and once humans are fatigued, it reduces their ability to verify the information they encounter. 8 Relating this to the pandemic, it could be argued that when individuals are overloaded with information, they are less likely to go extra trouble of verifying information sources and this could lead to the consumption and further proliferation of fake news.…”
Section: Cognitive Load Theorymentioning
confidence: 99%
“…Early research claimed that noise traders were not important to the formation of financial asset prices (Fama, 1965;Stephen, 1976;Khrennikova, 2016). Talwar et al (2021) looked at the decision-making process of investors from the perspective of psychology and pointed out that individual investors could easily be affected by emotional factors or cognitive biases, leading to unreasonable trading behaviors. Baker and Wurgler (2006) also proved that investor sentiment could affect stock returns.…”
Section: Investor Sentiment and Financial Assetsmentioning
confidence: 99%